Singapore : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The paper first uses the production function to analyze the sources of past growth in Singapore and compares it with the experience of other Asian and industrialized economies. This study also provides some thoughts on how to boost medium-term growth prospects in Singapore, and assesses the growth slowdown of the past few years in Singapore reflecting cyclical versus structural factors. The assessment given in this paper suggests that there are returns to be had from investment in education and structural reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet